INTERTEXTUALITY CONCEPT USED BY BRITISH ONLINE MEDIA REGARDING PRABOWO’S APPOINTMENT AS THE DEFENSE MINISTER (KONSEP INTERTEKSTUALITAS YANG DIGUNAKAN OLEH MEDIA ONLINE INGGRIS MENGENAI PENUNJUKAN PRABOWO SEBAGAI MENTERI PERTAHANAN) - Octavia Chandra Dewi; Heriyanto Heriyanto; Elvi Citraresmana (Balai Bahasa Jawa Barat, 2021)
The appointment of Prabowo as the Defense Minister in Jokowi’s cabinet had brought up the polemic, as the appointment was related to the preceding occasions of general elections and to the former general’s past actions. This study aims to analyze and describe the forms of intertextuality that appear in the British online news, regarding the appointment of Prabowo as the Defense Minister, and how the intertextual forms in the news texts influence the readers’ interpretation of the object of the news. This data is analyzed using the descriptive qualitative method and based on the intertextuality concept in the Critical Discourse Analysis approach suggested by Fairclough (1992). The source of the data analysis was the news texts in the British online media, TheGuardian.com. As the results, there are forty-five data consisting of various forms in the two dimensions of intertextuality: the manifest intertextuality and the interdiscursivity.